Analisis kondisi pasang surut dengan waktu kejadian gempabumi Sumatera Barat (Analysis of tidal conditions with the time of the earthquake in West Sumatera) - Elka Fitri Enora; Letmi Dwiridal (PILLAR OF PHYSICS, 2020)
Tides are a phenomenon of movement of the ups and downs of the surface of the sea water at intervals caused by a combination of the gravitational force and the attractive force of celestial bodies, especially by the sun, earth and moon. Earthquake events can occur from earth rock rock fractures by forces (including gravitational forces) that are collected slowly, and earthquakes can also occur if the stress shear causes the force to exceed the strength of the rock, causing deformation. Analysis of tidal conditions with the time of the West Sumatran earthquake in the period 2009-2019. The increase of tides in the period 2009 is on the 2009-09-30 has a depth of 79 km above sea level which is in the Mentawai Islands. Meanwhile, in the year 2010 there are 2010-10-25 has a depth of 10 km above sea level in the Mentawai Islands. In 2011 it was in the year 2011-08-04 had a depth of 41 km on sea level in the Mentawai Islands. While in the period 2016 there are 2016-06-01 has a depth of 69 km above the surface of the sea water in the Siberut estuary. In the period 2018 there are 21/04/2018 has a depth of 35 km are in the Siberut estuary.